2022
DOI: 10.48550/arxiv.2210.06044
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Multi-Granularity Cross-modal Alignment for Generalized Medical Visual Representation Learning

Abstract: Learning medical visual representations directly from paired radiology reports has become an emerging topic in representation learning. However, existing medical image-text joint learning methods are limited by instance or local supervision analysis, ignoring disease-level semantic correspondences. In this paper, we present a novel Multi-Granularity Cross-modal Alignment (MGCA) framework for generalized medical visual representation learning by harnessing the naturally exhibited semantic correspondences betwee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 46 publications
0
1
0
Order By: Relevance
“…Their study evaluated a novel approach using a publicly available lung nodule dataset, and the results demonstrated that employing the multi-granularity approach resulted in enhanced classification accuracy. In addition, Wang et al [39] provided a unique method for producing generalized visual representations for medical images using multigranularity cross-modal alignment. To assess the effectiveness of their approach, they used a variety of medical imaging datasets, including chest X-rays and mammograms.…”
Section: B Effect Of Multi-granularity On Classification Tasksmentioning
confidence: 99%
“…Their study evaluated a novel approach using a publicly available lung nodule dataset, and the results demonstrated that employing the multi-granularity approach resulted in enhanced classification accuracy. In addition, Wang et al [39] provided a unique method for producing generalized visual representations for medical images using multigranularity cross-modal alignment. To assess the effectiveness of their approach, they used a variety of medical imaging datasets, including chest X-rays and mammograms.…”
Section: B Effect Of Multi-granularity On Classification Tasksmentioning
confidence: 99%